Exploration of Locally Grown Yellow and Green Pumpkin as a Potential Source of b-Carotene and Vitamin A: Short Communication: Yellow and Green Pumpkin Source of Vitamin A - Zahra, Naseem; Nisa, Alim-un-; Hina, Sajila; Masood, Shahid; Kalim, Imran; Saeed, Muhammad Khalid; Ahmad, Ijaz; Arshad, Mahnoor (Biological Sciences - PJSIR, 2020)
Pumpkin is rich in beta-carotene which is used for preventing vitamin A deficiency. About 50 of carotenoids are the "Provitamin A compounds" which are precursors of retinol. Retinol is the active form of vitamin A. It plays an important role in vision. Beta carotene is an important anti-oxidant which protects the damaging of body cells by high free radical content because of its radical scavenging activity. The purpose of this study was to quantify the beta carotene and vitamin A present in yellow and green pumpkins. High performance liquid chromatography (HPLC) was used to analyze beta carotene and vitamin Yellow pumpkin contained the highest values of both the ?-carotene and vitamin A than green pumpkin. The results illustrated that green pumpkin (Curcurbita pepo) possess 20.3µg/g beta carotene; 52.6µg/g vitamin A and yellow pumpkin (Curcurbita maxima) contains 35.7µg/g beta carotene and 60.2 µg/g vitamin A in their pulp. It was concluded that there is a need to promote the use of locally available sources of carotene and retinol to overcome nutrition deficiency in the people.